Exact and Monte Carlo resampling procedures for the Wilcoxon-Mann-Whitney and Kruskal-Wallis tests. - Berry, Kenneth J.; Mielke, Paul W. (Perceptual & Motor Skills)
Exact and Monte Carlo resampling FORTRAN programs are described for the Wilcoxon-Mann-Whitney rank-sum test and the Kruskal-Wallis one-way analysis of variance for ranks test. The program algorithms compensate for tied values and do not depend on asymptotic approximations for probability values, unlike most algorithms contained in PC-based statistical software packages. Reprinted by permission of the publisher, 2000.